DAMPAK AKUNTANSI LINGKUNGAN TERHADAP KINERJA KEUANGAN PERUSAHAAN DI INDONESIA: SEBUAH STUDI LITERATUR - Magdalena Noviani Nayseo; Alfianus Oki; Beatrix Yunarti Manehat (P3M- Politeknik Negeri Kupang, 2023)
In recent years, the concept of green accounting has become increasingly popular as more and more companies realize the importance of environmental sustainability in their business. In a study on the impact of green accounting on business performance, researchers found that the use of green accounting can improve business performance in the long run. This is because there is a link between environment and sustainability with financial results. By taking environmental factors into account when measuring financial performance, companies can improve operations, reduce costs and increase long-term profits. In addition, green accounting can help companies identify environmental risks and develop strategies to manage these risks. In the long term, this can help companies reduce risk and maintain stable financial performance. Therefore the purpose of this study is to determine the impact of green accounting on company performance. This study used the library research method by reading and analyzing existing articles. This method instructs researchers to search, find, and analyze information from journals and articles. The results showed that the introduction of green accounting has positive effects such as efficient use of resources, corporate image, and continuity and negative effects such as additional costs to collect information in applying green accounting to company performance